Computational design and analysis of a roller pump flexible tube for delivering constant flow rate - Σάββα, Γιάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Ρευστών. Εργαστήριο Βιορευστομηχανικής και Βιοϊατρικής Τεχνολογίας, 2018)
Roller peristaltic pumps are used in various applications where fluid has to be isolated from the pumping mechanism. In the Biomedical field, they are used in drug infusion systems. An inherent drawback of peristaltic pumps is the periodic backflow observed on the outlet, based on the conservation of mass and it is caused by their operation principle. Aiming to suppress backflow, a number of approaches have been implemented so far. The work presented in this Master's thesis deals with the mass flow rate of a rotary peristaltic pump. Design and analysis are performed using coupled Computational Fluid Dynamics, CDF, with Computational Solid Mechanics, CSM, in a method called Fluid Structure Interaction, FSI. ANSYS Workbench system components were used; Transient Structural for the solid domain and Fluent for the fluid domain. A computational model of a rotary peristaltic pump is designed and tested using various approached. A simplified case of a circular cross section tube is studied in the beginning. An elliptic-like geometry is then used and finally, inflated tubes are investigated. Results have shown that backflow may be marginally suppressed using elliptic-like cross-sectional tube. Indirect fluid volume measurements on the simulated geometries revealed that inflated tubes exhibit no backflow and by tuning inflation design the magnitude of the pulsed flow may be decreased. Among the various cases examined, the most optimum is further studied and volumetric flow rate on the outlet is presented. Although still present, pulsed flow is greatly reduced with respect to cases with no inflation.